Dysphagia in children (0-12 years) recovering from tuberculosis meningitis (TBM) - Makanza, Wadzanai Michel (Division of Communication Sciences and Disorders, 2015)
Background information: Tuberculous meningitis (TBM) is the most severe extra-pulmonary complication of tuberculosis (TB) and also the most common bacterial meningitis in the Western Cape. The consequences of childhood TBM include poor motor and neurological outcomes which could lead to dysphagia. Aims: The aim of the study was to describe dysphagia in children (0-12 years) recovering from TBM at Red Cross War Memorial Children's Hospital (RCWMCH) in the Western Cape, South Africa. The purpose of the study was to determine the occurrence and describe the nature of dysphagia as well as to investigate whether any associations existed between dysphagia and the severity of TBM, neurological sequelae, age, and radiological findings.